Investigation on the influence of airflow on the acoustic performance of a single–Cylinder diesel engine exhaust muffler - Jun Fu; Milan Cheng; Yi Ma; Wei Zheng (PLoS ONE, 2025)
The airflow in the exhaust muffler can affect the sound propagation characteristics. In this work, For a single-cylinder diesel engine, an experimental bench was set up, and the accuracy of the simulation model was verified through the mutual comparison between the experimental data and the simulation results. the transmission loss of exhaust muffler of a single-cylinder diesel engine is analyzed numerically. In addition, the influence of airflow on the acoustic performance of muffler is studied and analyzed in detail. Finally, a finite element method, namely automatic matched layer (AML) is used to simulate the anechoic boundary conditions, and the value of transmission loss of muffler with and without airflow is calculated. Results demonstrate that: Considering the influence of airflow, the transmission loss value of the muffler shows the obvious increase in the low-frequency domain of 0–2000 Hz, particularly below 1000 Hz, with difference up to 50 dB and an average of approx. 30dB. Nevertheless, the airflow has minimal influence on transmission loss in the medium-high frequency of 2000–7000 Hz. The acoustic performance is greatly affected by the internal fluid flow, and the fluid flow is beneficial to improving the acoustic performance of mufflers, especially in the low-frequency domain. Additionally, the change of transmission loss curve is more complex when the influence of airflow is considered. The research results of this work provide a more accurate prediction method on the transmission loss in practical application, and of reference significance for future studies on the acoustic performance of mufflers.